Condensation of Amines with S -Methyl Thiouronium Salts: Another Entry for the Synthesis of Amidines - Swaroop, Toreshettahally R.; Bakyyev, Rahym; Rangappa, Kanchugarakoppal S.; Torun, Lokman (GEORG THIEME VERLAG KG, 2024)
We present a condensation of primary aryl or alkyl amineswith S-methyl thiouronium salts to obtain N,N,N '-trisubstituted amidines. High yields, short reaction times, and a fair substrate scope arethe noteworthy features of this protocol. Surprisingly, the reaction of athiouronium salt with 4-aminopyridine gave 1-(4-methoxybenzo-yl)piperidine.
Keywords: amidines; condensation; thiouronium salts; amides; amines; ELECTROPHILIC ACTIVATION; ALPHA-OXODITHIOESTERS; MILD METHOD; THIOAMIDES; EFFICIENT; DERIVATIVES; Chemistry